2021
DOI: 10.1021/acs.bioconjchem.1c00413
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Ubiquitin–Dioxetane Conjugate as a Chemiluminescent Probe for Monitoring Deubiquitinase Activity

Abstract: The removal of ubiquitin (Ub) from a modified protein or Ub chain is a process that occurs regularly by the ubiquitin–proteasome system. This process is known to be mediated by various deubiquitinating enzymes (DUBs) in order to control the protein’s half-life and its expression levels among many other signaling processes. Since the function of DUBs is also involved in numerous human diseases, such as cancer, there is an obvious need for an effective diagnostic probe that can monitor the activity of these enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…For example, Brik and Shabat reported that attaching the C-terminal sequence of ubiquitin protein (Ub(1–75)) to the aniline nitrogen through a glycine residue ( 85a ) allows an assay for deubiquitinase activity to be developed. 127 Since deubiquitinating enzymes are involved in various human diseases, monitoring of their activity is valuable. Probe 85a was found to be effective at detecting activity from three different deubiquitinases by cleavage of the scissile bond: UCH-L3, UCH-L1 and USP-2, with the first two giving the stronger response.…”
Section: Classes Of Self-immolative Elimination Pathwaysmentioning
confidence: 99%
“…For example, Brik and Shabat reported that attaching the C-terminal sequence of ubiquitin protein (Ub(1–75)) to the aniline nitrogen through a glycine residue ( 85a ) allows an assay for deubiquitinase activity to be developed. 127 Since deubiquitinating enzymes are involved in various human diseases, monitoring of their activity is valuable. Probe 85a was found to be effective at detecting activity from three different deubiquitinases by cleavage of the scissile bond: UCH-L3, UCH-L1 and USP-2, with the first two giving the stronger response.…”
Section: Classes Of Self-immolative Elimination Pathwaysmentioning
confidence: 99%
“… [6] Importantly, this groundbreaking development enabled the use of chemiluminescent probes as a sole component with no required additives. Numerous research groups worldwide, including ours, took advantage of the ortho ‐substituted phenoxy‐adamantyl‐1,2‐dioxetane luminophore to develop new useful chemiluminescent probes for detection and imaging of a variety of enzymes and analytes in living systems [7–21] …”
Section: Figurementioning
confidence: 99%
“…Numerous research groups worldwide, including ours, took advantage of the ortho-substituted phenoxy-adamantyl-1,2-dioxetane luminophore to develop new useful chemiluminescent probes for detection and imaging of a variety of enzymes and analytes in living systems. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Despite the encouraging progress in the field, further advancement has been limited by the synthetic inaccessibility of new dioxetane compounds. Typical synthetic methods for the preparation of phenoxy-dioxetane compounds are laborious and cannot be performed on substrates with unprotected functional groups.…”
mentioning
confidence: 99%
“… [6] Importantly, this game‐changer development enabled the use of chemiluminescent probes as a sole component with no required additives. Numerous research groups worldwide, including ours, took advantage of the ortho ‐substituted phenoxy‐adamantyl‐1,2‐dioxetane luminophore to develop useful chemiluminescent probes for detection and imaging of a variety of enzymes and analytes in living systems [7–27] …”
Section: Introductionmentioning
confidence: 99%